Rabies control in wildlife: the golden jackal (Canis aureus) requests for attention – a case study - Kemenszky, Péter; Jánoska, Ferenc; Nagy, Gábor; Csivincsik, Ágnes (Acta Agraria Kaposváriensis, 2020)
In Hungary, the rabies control programme with oral bait immunisation of wild carnivores dates back to 1992. Since than, the rules of vaccine placement on bait density has not changed, in spite of drastic expansion of both the carnivore community and the wild boar population in Europe. Though, all these elements of the concerned ecosystem compete for the baits. This case study was based on the accidental finding of vaccine blisters in jackal stomachs during a large-scale investigation on jackals’ feeding ecology. The results showed 3.17% (0.57-10.87%) frequency of bait occurrence in jackal specimens harvested during the vaccination term. This finding contradicted previous reports on high bait uptake rate and rabies seroconversion in golden jackals. These results called the attention the need for paradigm shift in management of diseases maintained in a natural reservoir. In the authors’ opinion, for reassuring result, multidisciplinary research groups should re-evaluate disease control strategies time and again.
Keywords: Golden Jackal; Multidisciplinary approach; Rabies control; Zoonotic diseases